Multidimensional evaluation of 3.0T HR-MRI, ultrasound imaging, and GATA3 protein expression in breast cancer, and their prognostic analysis - Bai, Yang; Xie, Ting; Mo, Xiangyang; Luo, Yong; Chen, Man (Frontiers in Oncology, 2025)
ObjectiveTo evaluate the diagnostic value of 3.0T high-resolution magnetic resonance imaging (3.0T HR-MRI), ultrasound imaging, and GATA3 protein expression in breast cancer (BC) and their prognostic implications.MethodsA retrospective analysis of 143 BC patients was conducted. All patients underwent preoperative 3.0T HR-MRI and ultrasound examinations. Diffusion tensor imaging (DTI) parameters, including mean diffusivity (MD), fractional anisotropy (FA), radial diffusivity (Dr), and axial diffusivity (Da), were assessed. Ultrasound features such as tumor morphology, vascularity, and posterior acoustic characteristics were analyzed. Immunohistochemistry was performed to detect GATA3 expression, and correlations with imaging parameters and prognosis were evaluated.ResultsGATA3 expression was significantly associated with BC pathological subtypes ( x2= 26.59, P < 0.0001). Compared with the GATA3-negative group, GATA3-positive tumors exhibited lower FA but higher MD, Dr, and Da values (P < 0.05), suggesting more preserved tissue structure. Ultrasound analysis showed that GATA3-positive tumors had less vascularity, posterior attenuation, and irregular margins (P < 0.05). Poor prognosis was associated with higher FA and lower MD, Dr, and Da values (P < 0.0001), as well as more aggressive ultrasound features. ROC analysis demonstrated superior prognostic performance when combining GATA3 expression, MRI, and ultrasound parameters (AUC = 0.9695, sensitivity = 83.54%, specificity = 96.88%).Conclusion3.0T HR-MRI and ultrasound provide complementary insights into BC characteristics. GATA3 expression is associated with better prognosis, and their combined analysis enhances diagnostic accuracy and prognostic evaluation.